Effects of moist dust/sand accretion on parabolic reflector antennas - Bashir, Saad Osman (IEE, 1997)
Theoretical results show that dust/sand accretion on reflector antennas is a real threat for slant-path communication systems, this includes satellite-to-Earth as well as high-low ground-to-ground microwave systems. Although little information on the accretion process is available it is guessed that under dry conditions these antennas will not form dust/sand layers more than a fraction of a millimeter thick, which will induce an attenuation of a fraction of a decibel; however, this will induce a beam shift of a fraction of a degree, which is significant to satellite communication systems. These threats are particularly significant in severe dust/sand storm countries. The moisture content of the dust is discussed